(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: To investigate the functional outcomes of modified trap door procedure with arthrodiastasis for avascular necrosis of femoral head. Methods: This case series study was conducted at Orthopaedic Surgery Department of Ghurki Trust Teaching Hospital, Lahore from January 2015 to December 2018. We analyzed all cases of osteonecrosis, diagnosed from clinical evaluation, radiographs, magnetic resonance imaging (MRI) and staged them using “Association Research Circulation Osseous classification (ARCO)” classification. Merle score was calculated pre-operatively and on follow-up assessments. Results: During the study period, 11 hips of 10 patients underwent the studied procedure. Out of these 10patients, 8(80.0%) were males and 2(20.0%) females. The mean age was 24.70±5.60 years ranging between 18-36 years. Mean duration of symptoms was 9.40±3.44 months. According to ARCO classification eight hips were classified as type-III and three hips as type-IV avascular necrosis of femoral head. Six (60.0%) patients had unilateral AVN and four (40.0%) had bilateral AVN. The mean duration of follow-up for patients was 42.8±6.4 months. After a period of three years following the procedure, a single patient had to undergo total hip replacement. No major complication occurred after surgery except infection in one patient, which settled down on removal of screws. Baseline Merle score was 6.20±1.40 while the mean post-surgery Merle score was 11.80±2.74 (p<0.0001) whereas the mean change in Merle score was 5.60±2.72 ranging between 0 to 10. Conclusion: Modified trapdoor procedure with hip distraction arthroplasty in advanced AVN reduces the pain and limitation of daily activities at average follow up of 43 months. This is a reasonable time buying procedure especially in patients not willing for replacement surgeries.